Embedding Formative Evaluation in Qur'an Literacy: A CIPPO Model Study in a Public Secondary School - Asniar Tanjung; Moh. Ali; A. Syathori; Agung (Educazione: Journal of Education and Learning, 2025)
Many students at general state secondary schools still cannot read or write the Qur'an correctly, yet the programs meant to address this weakness are seldom evaluated in any systematic way. This study evaluates the Qur'an literacy program at SMA Negeri 6 Konawe Selatan through the CIPPO model, which examines context, input, process, product, and output. The research used a qualitative descriptive-analytic design with a social phenomenological approach. Informants included the school principal, teachers, and students, chosen through purposive sampling. Data were gathered by interview, observation, and documentation, then analyzed through data reduction, data display, and conclusion drawing, while validity was secured through source, technique, and time triangulation together with member checking. The findings show that the program functioned well across all five components. Context evaluation confirmed a genuine need and a supporting module, input evaluation showed adequate resources and scheduling, and process evaluation recorded 70% of the monitored regular students reaching the minimum standard. Product evaluation verified sound attainment in reading and correct writing, and output evaluation yielded a mean score of 75.76 across 100 students. Notably, evaluation operated continuously within instruction rather than as a final audit, which allowed the teacher to correct weaknesses while learning was still underway. The study implies that schools can raise Qur'an literacy more effectively by embedding formative evaluation into everyday teaching, and it offers school leaders a practical basis for deciding whether to continue, revise, or strengthen such programs.